2020
DOI: 10.22146/jrekpros.56817
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kualitas Pelet Tandan Kosong Kelapa Sawit melalui Torefaksi Menggunakan Reaktor Counter-Flow Multi Baffle (COMB)

Abstract: Oil palm (Elaeis guineensis) empty fruit bunches (EFB) have not been utilized optimally. Currently, it is considered as a resource with low economic value. This biomass can be converted into bioenergy through a torrefaction process. Torrefaction is a mild pyrolysis at temperatures ranging between 200 and 300 °C, and it is generally performed under an inert atmosphere. The objective of this study was to evaluate the effects of torrefaction using Counter-Flow Multi Baffle (COMB) on the properties of oil palm EFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
4
0
3
Order By: Relevance
“…Bamboo betung pellets that have been torrefied at temperatures of 200 °C, 240 °C and 280 ℃ did not change shape and did not expand at all until observation within 24 hours. This is in line with the research conducted by Hidayat et al (2020) by conducting torrefaction on OPEFB pellets that did not experience significant changes after soaking for 12 hours. Another study by Iryani et al (2019) also stated that the pellets of palm oil empty fruit bunches that were not torrefied completely disintegrated in the 30minute test, while the pellets that had been torreffied did not change even after 12 hours of testing, indicating that they are good for long-term storage.…”
Section: Pellet Resistance To Watersupporting
confidence: 90%
See 1 more Smart Citation
“…Bamboo betung pellets that have been torrefied at temperatures of 200 °C, 240 °C and 280 ℃ did not change shape and did not expand at all until observation within 24 hours. This is in line with the research conducted by Hidayat et al (2020) by conducting torrefaction on OPEFB pellets that did not experience significant changes after soaking for 12 hours. Another study by Iryani et al (2019) also stated that the pellets of palm oil empty fruit bunches that were not torrefied completely disintegrated in the 30minute test, while the pellets that had been torreffied did not change even after 12 hours of testing, indicating that they are good for long-term storage.…”
Section: Pellet Resistance To Watersupporting
confidence: 90%
“…Purnomo et al (2022) conducted torrefaction of oil palm empty fruit bunches (OPEFB) pellets with a rotary reactor at a temperature of 260 °C for 35 minutes and reported that the torrefaction process produced pellets with low water content and hydrophobic properties so that their moisture absorption power was low. Hidayat et al (2020) also reported that OPEFB pellets torrefied with a Counter-Flow Multi Baffle (COMB) reactor with temperatures between 230 -280 °C had hydrophobic properties, so that when the water resistance test was carried out, there were no changes in the pellet form even after 12 hours of observation. Siyal et al (2020) conducted a torrefaction study on rice husk and sawdust pellets at temperatures of 230 °C, 280 °C, and 300 °C with residence times of 15, 30, 45, 60, and 120 minutes and reported that the torrefied pellets were ideal for long-term storage due to its hydrophobic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Hemicellulose will be decomposed first and followed by cellulose and lignin decomposition, respectively [10]. We have reported that torrefaction is able to improve fuel quality of biomass pellet made of oil palm empty fruit bunch [11][12][13][14][15]. The structure of the biomass changes in such a way that the material becomes brittle, and more hydrophobic.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass feedstocks are considered a renewable resource. However, biomass has several weaknesses compared to fossil fuels because it has high moisture content, lower in energy value and bulk density, high in mineral and oxygen contents, highly hygroscopic, and non-uniform in physical that make it difficult to handle [8,9].…”
Section: Introductionmentioning
confidence: 99%